Postpartum Depression in Young Mothers in Urban and Rural Indonesia - Alifa Syamantha Putri; Tri Wurisastuti; Indri Yunita Suryaputri; Rofingatul Mubasyiroh (Korean Society for Preventive Medicine, 2023)
Objectives Young mothers are vulnerable to postpartum depression due to role transition-related stress. Understanding the causes underlying these stressors is essential for developing effective interventions. Methods This study analyzed the 2018 Indonesian Basic Health Research data. The Mini International Neuropsychiatric Interview was used to assess postpartum depression symptoms in mothers aged 15-24 years with infants aged 0-6 months. In 1285 subjects, the risk factors for postpartum depression were evaluated using multivariate logistic regression. Results The overall prevalence of depression in the 6 months postpartum was 4.0%, with a higher prevalence in urban areas (5.7%) than in rural areas (2.9%). Urban and rural young mothers showed distinct postpartum depression risk factors. In urban areas, living without a husband (odds ratio [OR], 3.82; 95% confidence interval [CI], 1.24 to 11.76), experiencing preterm birth (OR, 4.67; 95% CI, 1.50 to 14.50), having pregnancy complications (OR, 3.03; 95% CI, 1.20 to 7.66), and having postpartum complications (OR, 5.23; 95% CI, 1.98 to 13.80) were associated with a higher risk of postpartum depression. In rural areas, postpartum depression was significantly associated with a smaller household size (OR, 3.22; 95% CI, 1.00 to 10.38), unwanted pregnancy (OR, 4.40; 95% CI, 1.15 to 16.86), and pregnancy complications (OR, 3.41; 95% CI, 1.31 to 8.88). Conclusions In both urban and rural contexts, postpartum depression relates to the availability of others to accompany young mothers throughout the postpartum period and offer support with reproductive issues. Support from the family and the healthcare system is essential to young mothers' mental health. The healthcare system needs to involve families to support young mothers' mental health from pregnancy until the postpartum period.